Copper removal from aqueous solution by marine green alga Ulva reticulata - Vijayaraghavan, Kuppusamy; Raj Jegan, Joseph; Palanivelu, Kandasamy; Velan, Manickam (Electronic Journal of Biotechnology, 2004)
The batch removal of copper (II) ions from aqueous solution under different experimental conditions using Ulva reticulata was investigated in this study. The copper (II) uptake was dependent on initial pH and initial copper concentration, with pH 5.5 being the optimum value. The equilibrium data were fitted using Langmuir and Freundlich isotherm model, with the maximum copper (II) uptake of 74.63 mg/g determined at a pH of 5.5. The Freundlich model regression resulted in high correlation coefficients and the model parameters were largely dependent on initial solution pH. At various initial copper (II) concentrations (250 to 1000 mg/L), sorption equilibrium was attained between 30 and 120 min. The copper (II) uptake by U. reticulata was best described by Pseudo-second order rate model and the rate constant, the initial sorption rate and the equilibrium sorption capacity were also reported. The elution efficiency for copper-desorption from U. reticulata was determined for 0.1 M HCl, H2SO4, HNO3 and CaCl2 at various Solid-to-Liquid ratios (S/L). The solution CaCl2 (0.1 M) in HCl at pH 3 was chosen to be the most suitable copper-desorbing agent. The biomass was also employed in three sorption-desorption cycles with 0.1 M CaCl2 (in HCl, pH 3) as the elutant.